Pendampingan Model Kurikulum Mutsallatsah dalam Optimalisasi Program “Maghrib Mengaji” di Kabupaten Pangandaran - Nurdiyanti, Yanti; Neneng Nurmalasari; Andi Abdul Hanafi (Universitas Muhammadiyah Surakarta, 2023)
The implementation of the Maghrib recitation program in Pangandaran Regency is still not optimal as can be seen from; the program runs only about 42%, the low ability to read the Koran for children, the right method is needed and there is no guideline for implementing the maghrib recitation program in Pangandaran Regency. The purpose of this service is to: Improve the maghrib recitation culture, realize the maghrib recitation program formulation, and fulfilling quality human resources in the religious field. The implementation of community service uses the Service Learning (SL) method with the following procedures: Brainstorming, Focus, Implementation, Evaluation and Reflection. The target of serving 22 Mosque Prosperity Councils (DKM) in Pangandaran Regency is to be carried out from November to December 2022. The results of this community service are as follows; 1) increasing children's motivation to attend the maghrib recitation, 2) implementation of the mutsallasah curriculum as a formulation in optimizing the maghrib recitation program in Pangandaran Regency, namely with the achievement target of the maghrib reciting focus on BTQ, Tahfidz and fahmil qur'an as well as an evaluation system 3) implementation of training for ustadz-ustadzah. So it was concluded that this court activity had an impact on increasing the implementation of the Maghrib recital in Pangandaran district with an ongoing mentoring program so that the Maghrib recital became an Islamic education laboratory for STIT NU Al Farabi Pangandaran.